Hepatitis B Virus Genotypes in the Kingdom of Bahrain: Prevalence, Gender Distribution and Impact on Hepatic Biomarkers - Janahi, Essam M. (Medicina (Kaunas), 2019)
Background: Approximately 400 million people are infected with Hepatitis B virus (HBV) around the world, which makes it one of the world’s major infectious diseases. The prevalence of HBV genotypes and predictive factors for risk are poorly known in the Kingdom of Bahrain. Objectives: The aim of the present study was to investigate the prevalence of HBV genotypes, its correlation with demographic factor sand impacts on hepatic biomarkers. Materials and Methods: Venous blood samples were collected from 82 HBV positive patients (48 males, 34 females). The extraction of HBV DNA, PCR amplification, and genotyping were done to classify different genotypes (A, A/D, B, B/D, C, D, D/E, E). HBV genotypes association with gender, nationality, mode of transmission, and liver cirrhosis complication was determined by descriptive statistic and univariate analysis of variance (ANOVA). For liver function test, unpaired t-test and ANOVA were performed. Results: The predominant genotype among patients under study was genotype D (61%), followed by genotype A (10%), and lowest frequency was found for undetermined genotype (1%). In general, there was no significant association between the different genotypes and some demographical factors, serological investigations, and liver function test. The prevalence of HBV genotypes was higher in male patients as compared to female patients and higher in non-Bahraini than in Bahraini. Patients with the dominant genotype D showed higher than the normal maximum range for alanine aminotransferase (ALT) (mean = 45.89) and Gamma-glutamyl transferase (GGT) (mean = 63.36). Conclusions: The most common HBV genotype in Bahrain was genotype D, followed by genotype A. Further studies involving the sources of transmission and impact of hepatic biomarker in Bahrain are required to enhance the control measures of HBV infections.